A Literature Review on Multicultural Business Communication (American Journal of Multidisciplinary Research and Innovation, 2023)
This thorough literature assessment digs into the complex world of multicultural corporate communication and examines the many factors that affect interactions in different cultural situations. Through systematic gathering of data from various published articles related to the topic, the review begins by putting good multicultural communication in the perspective of the current worldwide business environment. It sheds light on how cultural differences affect communication dynamics by analyzing subtle linguistic clues, nonverbal cues, and underlying cultural norms that influence cross-cultural interactions. Critical examinations of multicultural corporate communication’s difficulties and impediments highlight the dangers of misunderstanding, stereotyping, and communication breakdowns. In addition to promoting the development of cultural sensitivity, using efficient communication tools, and encouraging relationship-building and trust across cultures, the review highlights techniques to improve cross-cultural communication. The review examines the changing role of technology, intercultural leadership, and the ethical ramifications of multicultural corporate contacts to anticipate future developments in this field. This study offers helpful guidance for practitioners and organizations attempting to negotiate the challenging environment of multicultural corporate communication by summarizing the significant results and implications of the research. To address the changing opportunities and difficulties in this vital subject, the study ends with a plea for continued research and innovation